Essays on pricing strategy and market effects of new product introduction - Lin, Ying (Kansas State University, 2019)
This dissertation consists of two essays that analyze economic issues that fall within the sub-field of economics known as Industrial Organization. The essays focus on commercial aviation and coffee industries, respectively. The two essays maintain tight connections between economic theory and empirical analysis, and examine the observed economic phenomena in their respective markets in the past few years using econometric methods that are popular in Industrial Organization. The first essay investigates the U.S. domestic airlines’ pricing strategies in response to the significant worldwide decline in crude oil price beginning in mid-2014 through to 2015. Specifically, this essay examines the market mechanisms through which crude oil price may influence airfare, which facilitates identifying the possible market and airline-specific characteristics that may influence the extent to which crude oil price changes affect airfare. The essay first uses a simple theoretical model of air travel demand and Nash equilibrium price-setting behavior of airlines to derive clear theoretical predictions that guide proper specification of reduced-form regression models and help with interpreting empirical results. The empirical results reveal that there is a positive pass-through from changes in crude oil price to airfare, but the magnitude of the pass-through depends on several origin-destination market and airline-specific characteristics. In particular, the magnitude of the pass-through tends to be greater in more competitive origin-destination markets, smaller in longer distance markets, and smaller among airlines that purchase fuel using hedging contracts. The second essay analyzes the market effects of the introduction of single-cup coffee brew technology on the U.S. brew-at-home coffee market, particularly on the traditional auto-drip brew coffee segment. The introduction of single-cup coffee brew technology in the late 2000s has not only changed the way many brew-at-home coffee drinkers brew and consume coffee in daily life, i.e. a change from brewing one “pot” at a time to making one cup at a time, but also altered the overall landscape of the brew-at-home coffee market in the U.S. This paper analyses the economic impacts in the U.S. brew-at-home coffee market associated with the introduction and growing presence of single-cup coffee brew technology. We find that a typical coffee drinker is willing to pay up to 2.52 cents extra per fluid ounce to consume freshly brewed coffee from single-cup brewing machines instead of using the traditional auto-drip brewing method, and this marginal willingness to pay gap increases with consumers’ income level. Second, we find that both the demand and profitability of traditional auto-drip brew coffee products are substantially lower owing to the growing consumer valuation of single-cup brew technology. Last, our analysis reveals that consumers enjoy substantially higher welfare owing to the introduction and growing popularity of single-cup brew coffee products.
Keywords: Cost pass-through; Airline pricing; Single-cup brew coffee; Traditional auto-drip brew coffee; Willingness to pay; Brew-at-home coffee market